Visual Identity System of a Dental Laboratory - Lupu Iulian Costin; Nicolae Gherman; Carausu Elena Mihaela (Romanian Society of Oral Rehabilitation, 2012)
The growing competition in the segment of medical services has introduced the need for clear differentiation and, also, the need for increased visibility. The dental laboratories has to promote the quality of their services, of the materials that they are using, the continuously need for novelty, and never the less the successfully and growing relationships with the dental practices, ("We grow together") Therefore, having a strong identity system, that is also in accordance with the values, that want to be promoted, is very important.